RUSSIAN ENERGY COMPANIES IN CENTRAL ASIA - GUSEYNOV, Rauf (CENTRAL ASIA AND THE CAUCASUS, 2004)
Recently, the largest Russian oil and gas companies have turned their attention to Central Asia and have been developing their cooperation with the post-Soviet republics in various forms and with different results. Their successes will allow Moscow to recapture the positions that until recently looked as lost forever to Western rivals. The Russian firms stepped up their activity in 2001 when the geopolitical situation had changed dramatically: the counter-terrorist operation in Afghanistan brought American military bases to the region, while the United States started seeking clos-er political and economic ties with the new independent states.